Detoxification of heavy metals by microbial preparation with methane production - Bida, Iryna; Havryliuk, Olesia; Hovorukha, Vira; Tashyriev, Oleksandr; Yastremska, Larysa (Problems of Environmental Biotechnology, 2024)
The aim of the study was to theoretically substantiate and experimentally confirm the ways of precipitation of soluble toxic metals Co2+, Ni2+ and CrO2-4 using a microbial preparation based on non-adapted anaerobic microorganisms of biohumus and biogas plant sludge.